Further information on Lolibaia Gorbunov & Gurko, 2017 (Lepidoptera: Sesiidae: Synanthedonini) with description of three new species from tropical Africa - Bartsch, Daniel; Sáfián, Szabolcs (Zootaxa, 2019)
The knowledge of the clearwing moth genus Lolibaia Gorbunov & Gurko, 2017, recently described from South Sudan and until now known only from a single, damaged specimen, is extended by three new species from different parts of Africa including the as yet unknown female of the genus. L. jurateae sp. nov. is based on a single male from Kakamega Forest, Kenya; L. triangularis sp. nov. is based on six males from different localities in north-western Zambia, and L. polythyris sp. nov. is described from two females from the Eastern Cape and KwaZulu-Natal Provinces, South Africa.